Study and numerical analysis of Von Mises stress of a new tumor-type distal femoral prosthesis comprising a peek composite reinforced with carbon fibers: finite element analysis. Issue 15 (31st October 2022) - Guo, Yu; Guo, Wei
Abstract: Research on carbon-fiber-reinforced polyetheretherketone (CF-PEEK/CFR-PEEK) as a bone tumor joint prosthesis remains limited. Herein we numerically determine the feasibility of CF-PEEK material containing 30% Wt carbon fiber (CF30-PEEK) as a material for the dual-action tumor-type distal femoral prosthesis. Use CT scan method to build a complete finite element model of the knee joint. Simulate the resection of the distal femoral tumor, and then reconstruct it with the dual-action tumor-type distal femoral prosthesis. The femoral condyle and extension rod components were simulated with cobalt chromium molybdenum (CoCrMo), PEEK and CF30-PEEK materials respectively. When simulating the standing state, a vertical stress of 700 N is applied to the femoral head. When simulating the squatting state, a vertical stress of 2800 N is applied to the femoral head. The displacement and rotation angle of each node of the distal tibia are fully restrained in three directions (X-axis, Y-axis, Z-axis). We examined the stress magnitude, stress distribution, and stability of the prosthesis and each of its components by means of finite element analysis (FE analysis). The FE analysis results show: after replacing the distal femur and the extension rod with CF30-PEEK material, the stress is still evenly distributed, and the average stress is significantly reduced. In addition, the stability is similar to CoCrMo material. Therefore, CF30-PEEK is an appropriate material for this type of prosthesis.